Effect of Organizational Career Program on Employees' Career Commitment: An Islamic Perspective. - Nurziyanti, Mohamad Khan; Azman, Ismail; Wan Aishah, Wan Mohd Nowalid; Nurul Hayati, Adnan; Nazatul Shima, Abdul Rani (2014)
According to human resource development literature based on Islamic perspective, organizational career program consists of two major dimensions: career management and career development. Recent studies in this field highlight the ability of management to provide appropriate support for individual employee to progress in his/her career path may lead to career commitment. Nevertheless, the role of career program as important determinant is given less attention in the literature. Therefore, this study was undertaken to examine the relationship between organizational career program and employees’ career commitment using 200 self-report questionnaires gathered from employees at a selected public university in Malaysia. The outcomes of SmartPLS version 2.0 showed that organizational career program (i.e, career management and career development) was positively and significantly related to career commitment. This result confirms that organizational career program does act as an important determinant of employees’ career commitment in the studied organization. Further, discussion, implications and conclusion are elaborated.